2020
DOI: 10.1007/s11606-020-05736-y
|View full text |Cite
|
Sign up to set email alerts
|

Student Education About Pre-exposure Prophylaxis (PrEP) Varies Between Regions of the United States

Abstract: BACKGROUND: Daily, oral pre-exposure prophylaxis (PrEP) is an effective and safe prevention strategy for people at risk for HIV. However, prescription of PrEP has been limited for patients at the highest risk. Disparities in PrEP prescription are pronounced among racial and gender minority patients. A significant body of literature indicates that practicing healthcare providers have little awareness and knowledge of PrEP. Very little work has investigated the education about PrEP among health professionals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 83 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…2 ). This could suggest incongruence between where PrEP is most needed and where pharmacists are likely to be familiar with PrEP [ 57 ]. This finding could also suggest that pharmacists in areas with high HIV rates are already familiar with PrEP, indicating a more critical need for evaluation of pharmacist knowledge of PrEP in other U.S. regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). This could suggest incongruence between where PrEP is most needed and where pharmacists are likely to be familiar with PrEP [ 57 ]. This finding could also suggest that pharmacists in areas with high HIV rates are already familiar with PrEP, indicating a more critical need for evaluation of pharmacist knowledge of PrEP in other U.S. regions.…”
Section: Discussionmentioning
confidence: 99%
“…For future pharmacists currently receiving PharmD curriculum, studies showed increasing integration of PrEP education into PharmD programs, providing data from all four regions of the U.S. [ 57 ]. No qualitative or longitudinal studies measured pharmacy student knowledge of or attitudes toward PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of research on PrEP in heterosexual men in the context of the United States. Heterosexual men are among the least likely populations to be presented to healthcare providers as potential PrEP candidates in PrEP-related training curriculum across all regions of the U.S. [50]. This trend may impact the degree to which healthcare providers perceive heterosexual men as candidates for PrEP despite there being PrEP eligibility criteria that are relevant to heterosexual men (e.g.…”
Section: Differences By Sexual Identitymentioning
confidence: 99%
“…This over-representation is due to a majority of the schools that participated in this study being located in the Midwestern U.S. For this reason, we included region as a covariate. A future study may benefit from targeted investigation of PrEP/HIV knowledge in the Southern U.S. given the region’s high HIV burden and previous work showing sub-optimal health professions education about PrEP in the Southern U.S ( Bunting et al, 2020 ). We were unable to compare the demographics of our sample to the demographic composition of the students who did not respond as we did not have access to the demographic details of the student bodies at all participating institutions.…”
Section: Limitationsmentioning
confidence: 99%
“…Ensuring current disparities in HIV incidence and PrEP prescription are not propagated requires educating health professionals in training about HIV-prevention in the biomedical era. Previous work evaluating health professions curriculum has found that medical and pharmacy students receive inadequate training about PrEP effectiveness, patient indications, and PrEP and HIV disparities, and that over 30% of fourth-year medical and pharmacy students did not receive training about PrEP ( Bunting et al, 2020 ). A national study of medical and pharmacy students conducted in 2019 found that students were unsure of the connection between PrEP and widespread HIV-resistance, and which patient populations are indicated for PrEP ( Bunting et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%